Climatic Trends and Their Impacts on High-Altitude Ecosystems in Nepal: Implications for Biodiversity and Ecosystem Services - Ghimire, Narayan Prasad; Ghimire, Puja; Chauhan, Raju; Thakuri, Sudeep (Journal of Environment Sciences, 2025)
Nepal’s high-altitude ecosystems (>3000 m asl) are experiencing unprecedented impacts from climate change, with profound implications for biodiversity conservation and ecosystem services. This systematic review synthesizes evidence from 72 peer-reviewed studies to assess climatic trends and their ecological consequences in the Nepal Himalaya. Temperature records from 1976-2015 reveal significant warming trends, with higher elevations experiencing more pronounced increases (0.045°C y–1 for maximum temperatures). Climate projections indicate continued warming of 1.2-4.2°C by the 2080s under RCP8.5 scenarios, with precipitation increases of 11-23% by 2100. These climatic changes are driving cascading ecosystem effects. Glacial retreat has accelerated, with 15% reduction in glacier surface area over five decades and upward snowline shifts of 182 m in the Everest region. Freshwater ecosystems face mounting pressures from altered hydrology and increased glacial lake outburst flood risks. Forest ecosystems exhibit treeline advance (2.61 m y–1 for Abies spectabilis), phenological shifts, and upslope vegetation migration. Biodiversity impacts include altered species distributions, invasive species expansion, and habitat degradation for endemic species. The convergence of warming temperatures, changing precipitation patterns, and extreme weather events poses significant threats to Nepal’s mountain biodiversity hotspots and ecosystem services. These findings present the urgent need for integrated climate adaptation strategies and science-based conservation approaches to safeguard these vulnerable ecosystems. Nepal’s mountainous regions serve as both indicators of global climate change and critical refugia requiring immediate conservation attention to maintain ecological integrity.